The obesity gap: An investigation using the behavioral risk factor surveillance system data for Ohio - Karen H Larwin; Sherri Harper Woods (Intelektual Pustaka Media Utama, 2021)
This investigation examined potential predictors of obesity and whether an “obesity gap” is present for different demographic groups. The behavioral risk factor surveillance system (BRFSS) data was used for this investigation. This secondary data set provides self-reported and measured biometric information on residents from each state in the United State of America. Results indicated that different income level is not related to body mass index (BMI). However, BMI was significantly different if the individual had a previous diagnosis of diabetes. BMI was also found to be significantly different for different races, as well as the interaction between race and diabetes are associated with BMI.